Inhibitors for the provision of quality education in the selected rural secondary schools from school governance perspective - Mavuso, Mzuyanda Percival; Tomose, Zimisele Raymond; Olawumi, Kayode Babatunde (CV. AFDIFAL MAJU BERKAH, 2024)
Over the years, South Africa has experienced a downward trend in the quality of education at the inception of democracy. Statistics from the Department of Basic Education on the matric results from 2014 to 2016 indicate a downward trend in learners' academic performance from the Eastern Cape Province. This is even though SGB is amongst the major stakeholders tasked to promote the quality of education in schools. This paper, therefore, explored the inhibitors to the quality of education in three rural secondary schools in Buffalo City Metro Education District from a point of school governance perspective. Since this study was premised on a qualitative approach, semi-structured interviews were used to collect data from participants. Twenty-two participants were drawn from eighteen SGB members, two secondary school principals, and two Education Development Officers. This paper used the school effectiveness framework as a lens to explain the inhibitors to the quality of education in the selected rural secondary schools from a school governance perspective. Findings reveal a lack of capacitation of SGB by school leadership and the Department of Basic Education (DBE), divergent views about the role of school leadership in ensuring effective school governance, and how SGB is involved in financial matters Therefore, this paper recommends that the DBE organize extensive training programmes to capacitate school leaders and SGB members on school governance issue, provide supervisory roles in the management of school funding regularly in line with the provision of the SASA 1996